Characterization of copy number alterations in a mouse model of fibrosis‐associated hepatocellular carcinoma reveals concordance with human disease. (18th January 2016) - Chappell, Grace; Silva, Grace O.; Uehara, Takeki; Pogribny, Igor P.; Rusyn, Ivan
Abstract: Hepatocellular carcinoma (HCC) is a prevalent human cancer with rising incidence worldwide. Human HCC is frequently associated with chronic liver inflammation and cirrhosis, pathophysiological processes that are a consequence of chronic viral infection, disturbances in metabolism, or exposure to chemical toxicants. To better characterize the pathogenesis of HCC, we used a human disease‐relevant mouse model of fibrosis‐associated hepatocarcinogenesis. In this model, marked liver tumor response caused by the promutagenic chemical N ‐nitrosodiethylamine in the presence of liver fibrosis was associated with epigenetic events indicative of genomic instability. Therefore, we hypothesized that DNA copy number alterations (CNAs), a feature of genomic instability and a common characteristic of cancer, are concordant between human HCC and mouse models of fibrosis‐associated hepatocarcinogenesis. We evaluated DNA CNAs and changes in gene expression in the mouse liver (normal, tumor, and nontumor fibrotic tissues). Additionally, we compared our findings to DNA CNAs in human HCC cases (tumor and nontumor cirrhotic/fibrotic tissues) using publicly available data from The Cancer Genome Atlas (TCGA). We observed that while fibrotic liver tissue is largely devoid of DNA CNAs, highly frequently occurring DNA CNAs are found in mouse tumors, which is indicative of a profound increase in chromosomal instability in HCC. The cross‐species gene‐level comparison of CNAs identified shared regions of CNAs between human fibrosis‐ and cirrhosis‐associated liver tumors and mouse fibrosis‐associated HCC. Our results suggest that CNAs most commonly arise in neoplastic tissue rather than in fibrotic or cirrhotic liver, and demonstrate the utility of this mouse model in replicating the molecular features of human HCC. Abstract : This report demonstrates an accumulation of copy number alterations (CNAs) in liver tumors but not in surrounding preneoplastic liver tissue, in both human clinical samples and in a mouse model of fibrosis‐associated hepatocellular carcinoma (HCC). These findings, together with previous results demonstrating increased epigenetic alterations indicative of genomic instability, suggest that chromosomal instability is a feature of tumor cells that precedes common mutations. Many of the segments with altered copy number, as well as the genes within those segments, were observed in liver tumors from both mice and humans, demonstrating the relevance of the mouse fibrosis‐associated liver cancer model to human HCC.